Effect of Cryopreservation on Pluripotency Gene Expression in Ehrlich Carcinoma Cells of Different Terms of Development - Chelombitko, Olga V.; Bondarovich, Nikolay A.; Ostankov, Maksim V.; Dimitrov, Aleksey Yu.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2015)
N/A